Produktivitas dan pertumbuhan industri di Indonesia - Agus Widarjono (Universitas Islam Indonesia, 1997)
An industrilization is a strategic effort to restructure economy and to change society's life because it can transform an agricultural society that is static to become an industrial society that is dinamic.